(untitled) (Research, Society and Development, 2021)
Feline breast hyperplasia (FBH) is a non-neoplastic disorder, characterized by cellular proliferation of the duct stroma of the mammary glands, commonly diagnosed in Brazil. Such change is often caused by the inappropriate use of exogenous progestogens in cats, which can be stored in the organism of the animal, and sensitize the glands to the proliferation exacerbated by hormonal stimulus. One of the factors associated with recurrent cases of FBH is the sale of these drugs in stores that provide service for the sale of veterinary products, applied without restrictions and without knowledge of feline physiology, in an attempt to control pregnancy. The awareness of owners about the harms of uncontrolled application of progestins and the stimulation of them to opt for surgical sterilization of their animals should be done by veterinarians, in order to avoid further complications such as breast cancer, thus ensuring greater welfare of the feline population. The purpose of this review is to address epidemiological, physiological and clinical aspects, and to promote an allusion to the indiscriminate use of contraceptives in this species.